The humanization of chemical species. "Path to the hidden reality". - Anunziata, Oscar Alfredo (Univesidsad Tecnológica Nacional, 2023)
This work is multidisciplinary and brings together aspects of Quantum Physic chemistry, Physics, Chemistry and Epistemology/Semiotics. By exploring topics ranging from materials to design, it alsoseeks to elucidate the underlying connections between the natural (visible reality) and the artificial (hidden reality), and experiment and modeling. The results are intended to contain elements of discovery and surprise that often accompany the gainingof new knowledge toward a new conception of the architecture and function of the mass of matter and energy that sustains our thoughts. We conceive of Reality as everything that is detected by our senses, and especially that which is visible to our eyes, or which, aided by the development of high-tech equipment, we can detect. Nevertheless, isthis reality the only one? This conception does not explain phenomena that occur in the Cosmological Nature, so my proposal is that other "Hidden" realities exist but we do not detect them, or that they simply do not exist. After "humanizing" (giving the attribution of thinking, responding, acting), to species that we do not conceive to have "Life" such as atoms, to cite one, every particle that makes up the mass of matter andenergy of the Universe led me to the "creation of a New chemical species" (C-Zr-SO4H2), recently reported1 . This attribution ascribed to mass/energetic species, without neural systems, led me after three years toconceive the Idea of Hidden Reality and to generate a possible mechanism (architecture), of how we think when our objective is to hit an “invisible target”, or to "create" new targets. Abstraction. The symbolic abstraction (inscrutable variables). Abstract Symbolism (parameterization of abstract variables). Symbolic Reality (expression of mass of matter or energy indefinite, but symbolized).Real Symbolism (parameterization of functional variables that replicate the Hidden Reality). From HiddenReality to Detectable Reality.
Keywords: Quantum physic chemistry; Epistemology; Semiotics